Adsolubilization and stability characteristics of hydrocarbon aggregates chemically bonded to porous silica - Thakulsukanant, Chainarong; Lobban, Lance L.; Osuwan, Somchai; Waritswat, Anchaleeporn (My University, 1997)
The desorption of surfactant may be a problem in the development of admicellar catalysis for organic synthesis or for wastewater cleanup. The formation of hydrocarbon aggregates chemically bonded to mineral oxide surfaces has been investigated to solve this problem. In this study, octadecyltrichlorosilane (ODS) was chemically bonded with silanol groups of a silica surface. The adsolubilization capabilities and stability of the bonded ODS were then studied and compared to those of physically adsorbed aggregates of cetyltrimethylammonium bromide (CTAB). The adsorption of ODS increases with increasing ODS concentration in the bulk phase and reaches a constant value when the equilibrium ODS concentration is higher than 17 000 μM. The maximum ODS adsorption of 340 μmol/g is slightly higher than that of CTAB (300 μmol/g). The critical micelle concentration of CTAB is approximately 3000 μM. The adsolubilization of two organic substrates, trichloroethylene (TCE) and phenol, was also measured. The adsolubilization of TCE was similar in CTAB and bonded ODS, while the phenol adsolubilized to a greater extent in CTAB than in ODS. The bonded ODS was stable under agitation up to 310 rpm and temperatures below 40 °C. The pH value has very little effect on ODS debonding. The rate of oxidation of ODS by ozone increases with increasing ozone concentration, but pH has no effect on ODS oxidation.